Hubungan Tekanan Darah Sistolik Dengan Kadar Trigliserida Pada Pasien Diabetes Melitus Tipe 2 Di Klinik Arafah Lampung Tengah - Toni Prasetia; Firhat Esfandiari; Sandhy Arya Pratama; Mohamad Imam Istawa (Universitas Malahayati, 2021)
ABSTRACT: CORRELATION OF SYSTOLIC BLOOD PRESSURE WITH TRIGLYCERIDE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS IN ARAFAH CLINIC, CENTRAL LAMPUNGBackground: Hypertension is the main risk factor for DM. Hypertension can make cells insensitive to insulin. Even though insulin plays a role in increasing glucose uptake in many cells and in this way also regulates carbohydrate metabolism, so that if insulin resistance occurs by cells, the blood sugar levels can also be disrupted. Dyslipidemia is a change in blood lipid profile, one of which is an increase in triglyceride levels. High triglyceride levels can cause thickening of the blood vessels and cause narrowing of the arteries.Objective: To determine the relationship between systolic blood pressure and triglyceride levels in patients with type 2 diabetes mellitus in Klniki Arafah Tengah Lampung.Methodology: This research uses a descriptive-analytic research method with a cross-sectional approach. The sampling technique is Total Sampling. . Respondents in this study were patients with Type 2 Diabetes Mellitus at the Arafah Clinic in Central Lampung in 2020.Results: It is known that in the sex frequency distribution, there were 16 men with 34.8% and 30 women with 65.2%. Distribution of frequency based on age, it was found that the age group 24-45 years numbered 7 patients (15.2%), the age group 46-65 years amounted to 32 patients (69.6%), and the group> 65 years amounted to 7 patients (15.2 %). It is known that the frequency distribution of systolic blood pressure in type II diabetes mellitus patients, it was found that type II diabetes mellitus patients with normal systolic blood pressure levels were 34 patients with 73.9%, while high systolic blood pressure levels were 12 patients with 26.1%. It is known that the frequency distribution of triglyceride levels in patients with type II diabetes mellitus, it was found that 8 patients with normal triglycerides had normal triglyceride levels, and 38 patients (82.6%) had high triglyceride levels. The results of the chi-square statistical test found no relationship with the results of p = 898 (p> 0.05).Conclusion: There is no correlation between systolic blood pressure and cholesterol triglycerides in type 2 diabetes mellitus patients at the Arafah Clinic, Central Lampung in 2020. Keywords: Type 2 Diabetes Mellitus, Systolic Blood Pressure Triglierida INTISARI: HUBUNGAN TEKANAN DARAH SISTOLIK DENGAN KADAR TRIGLISERIDA PADA PASIEN DIABETES MELITUS TIPE 2 DI KLINIK ARAFAH LAMPUNG TENGAHLatar Belakang: Hipertensi merupakan faktor risiko untama untuk terjadinya DM. Hipertensi dapat membuat sel tidak sensitif terhadap insulin. Padahal insulin berperan meningkatkan ambilan glukosa di banyak sel dan dengan cara ini juga mengatur metabolisme karbohidrat, sehingga jika terjadi resistensi insulin oleh sel, maka kadar gula di dalam darah juga dapat mengalami gangguan. Dislipidemia adalah perubahan dari profil lipid darah salah satunya adalah peningkatan kadar trigliserida. Kadar trigliserida yang tinggi dapat menyebabkan penebalan pembuluh darah dan menyebabkan penyempitan pembuluh darahTujuan : Untuk mengetahui hubungan tekanan darah sistolik dengan kadar trigliserida pada pasien diabetes melitus tipe 2 di klniki arafah lampung tengahMetode : Jenis penelitian ini menggunakan metode penelitian deskriptif analitik dengan pendekatan cross – sectional. Teknik pengambilan sampel berupa Total Sampling. . Responden dalam penelitian ini adalah pasien Diabetes Melitus tipe 2 di Klinik Arafah Lampung Tengah tahun 2020.Hasil : pada variabel trigliserida dan tekanan darah sistolik diperoleh nilai p Vale = 898 (p>0,05)Kesimpulan: Tidak terdapat Hubungan Antara Tekanan Darah Sistolik dengan Trigliserida Kolesterol pada pasien Diabetes Melitus tipe 2 di Klinik Arafah Lampung Tengah tahun 2020.Kata Kunci : Diabetes Melitus tipe 2, Tekanan Darah Sistolil Triglierid